A Rare Cause of Leg Ulcer: Calcinosis Cutis as a Part of CREST Syndrome. (December 2018) - Odyakmaz Demirsoy, Evren; Çatal, Cansu; Yazıcı, Ayten; Bayramgurler, Dilek
Leg ulcers are not a disease themselves, they are a symptom of a disease. To manage them properly, finding the correct diagnosis of the disease is mandatory. Our case is a model to underline that leg ulcers are a significant burden for the patient, because leg ulcer got ahead of the patient's other serious complaints such as Raynaud's phenomenon or sclerodactyly. Furthermore, our patient is also a model, and an attentive clinical evaluation is inevitable to find the correct diagnosis. We present our case aiming to underline the significance of full dermatologic examination in each ulceration to discover underlying disease.